Role of SGLT2 inhibitors in improving cardiac functions (on Echocardiography) in patients having Diabetes Mellitus and ischemic heart disease - Owais, Muhammd; Ghulam Abbas Tahir; Yasir Yaqoob; Usman Musharaf; Abdul Wahid; Ayesha Izat (Journal of University Medical & Dental College, 2024)
BACKGROUND & OBJECTIVE: Sodium-glucose cotransporter-2 inhibitors (SGLT2i or SGLT2 inhibitors) have a distinctive mechanism of action unrelated to insulin secretion or action. By causing glucosuria, they reduce plasma glucose by inhibiting SGLT2 in the proximal tubules of the kidneys. This mechanism of action corrects several metabolic abnormalities, which are, in fact, CVD risks in addition to normoglycemia. This study was conducted to assess the average change in ejection fraction resulting from the use of SGLT2 inhibitors in enhancing cardiac function in patients with Diabetes Mellitus and ischemic heart disease. METHODOLOGY: This is a descriptive case series conducted from 10th December 2022 to 9th May 2023 in the Department of Medicine, Faisalabad Medical University; 435 type II diabetes mellitus patients were selected, according to inclusion and exclusion criteria. All received a daily dose of 20 mg of SGLT2 for three months. Echocardiography was done before and after the treatment period left ventricular ejection fraction (EF) was evaluated, and improvement in cardiac function was noted. RESULTS: In this study, the mean age of participants was 46.54±8.52 years. 314 (72.18%), or the majority, were between 30 and 50. The male-to-female ratio was 1.1:1, with 228 (52.41%) men and 207 (47.59%) women. The mean ejection fraction at baseline was 53.45 ± 4.12. The mean change in ejection fraction of SGLT2 inhibitors in improving cardiac functions among patients having Diabetes Mellitus and ischemic heart disease was 50.79 ± 3.76.( p-value ≤0.001). CONCLUSION: SGLT2 inhibitors effectively improve cardiac functions among patients with Diabetes Mellitus type II and ischemic heart insult